2017
DOI: 10.1139/bcb-2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting lactoferrin concentration in human milk: how much do we know?

Abstract: Lactoferrin (LF) is a breast milk glycoprotein with antimicrobial and anti-inflammatory effects. Its beneficial properties in infants, especially in those born preterm, are currently being studied in clinical trials. However, the maternal and nursing infant factors that may affect the concentration of LF in breast milk are still not clear. We conducted a systematic review to investigate the factors that may affect LF concentration. We used a 2-step approach to identify the eligible studies according to inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 95 publications
(125 reference statements)
2
26
0
1
Order By: Relevance
“…In the case of lactoferrin the mean concentration detected in raw milk samples was 1.63 ± 0.47 mg/ml (range 1.17–2.11 mg/ml) which is similar to those reported in the literature ( 39 ) (Table 1 ) The reduction of lactoferrin level by HoP in current experiments is 60% of the level detected in raw milk samples. The difference was statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…In the case of lactoferrin the mean concentration detected in raw milk samples was 1.63 ± 0.47 mg/ml (range 1.17–2.11 mg/ml) which is similar to those reported in the literature ( 39 ) (Table 1 ) The reduction of lactoferrin level by HoP in current experiments is 60% of the level detected in raw milk samples. The difference was statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…Several maternal factors significantly corrected with the Lf concentration in human milk. A previous review of factors that affect the concentration of Lf in breast milk revealed conflicting reports of the relationship of maternal factors to breast milk Lf [ 30 ]. The present study showed that maternal age, maternal BMI, mode of delivery, parity, maternal serum albumin level, and protein intake were not significantly correlated with milk Lf concentration, whereas the amount of milk expressed from one breast and maternal serum ferritin were negatively correlated with milk Lf concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It is a member of the transferrin family of proteins and strongly binds iron [88]. The amount of lactoferrin in the milk varies depending on the stage of lactation as colostrum contains a high concentration of lactoferrin and it slowly decreases through the first month of lactation [89,90]. The reduced digestive capacity of the infant intestine protects milk-derived lactoferrin from degradation and maintains its functional properties, thus restricting the growth of bacteria in early life [91].…”
Section: Lactoferrin and Other Anti-bacterial Proteins Found In Milkmentioning
confidence: 99%